Polyester and its preparation method and application

By controlling the content and molecular weight distribution of low-molecular weight substances in polyester, the surface precipitation and fluidity problems of aliphatic polyester products are solved, and the balanced effect of high gloss and good fluidity is achieved.

CN114957628BActive Publication Date: 2025-03-11ZHUHAI KINGFA BIOMATERIAL CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210569210.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-24
Publication Date
2025-03-11
Estimated Expiration
2042-05-24

AI Technical Summary

Technical Problem

Aliphatic polyester products often have problems such as small molecules on the surface precipitation and gloss disappearing, and their melt viscosity is high, which leads to problems such as melt glue deficiency during injection molding.

Method used

By controlling the total content of low molecular weight substances in the polyester between 0.1-0.6 wt%, and the integral area of ​​the peak with a number average molecular weight Mn greater than 400 in the GPC curve is less than 60% of the total integral area, the precipitation problem and fluidity of the polyester are improved.

Benefits of technology

The high gloss and good fluidity of the polyester product are achieved, so that the gloss and fluidity of the product are maintained in an equilibrium state, avoiding additional processing steps and cost increase.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114957628B_ABST
    Figure CN114957628B_ABST
Patent Text Reader

Abstract

The present invention discloses a polyester and a preparation method and application thereof, wherein the total content of low molecular weight substances in the polyester is 0.1-0.6wt%, and the GPC curve of the low molecular weight substances has the following characteristics: the integral area of ​​the peak with a number average molecular weight Mn greater than 400 is less than 60% of the total integral area. The present invention can effectively solve the problem of easy precipitation on the surface of polyester products, and the prepared polyester product has high gloss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biodegradable polyesters, and in particular to a polyester with a relatively low content of low molecular weight substances and a preparation method and application thereof. Background Art

[0002] Thermoplastic aromatic polyesters, which are widely used in industry and daily life, have excellent thermal stability and mechanical properties, are easy to process and are inexpensive. For example, polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) have been widely used in the manufacture of fibers, films and containers. However, these aromatic polyesters are difficult to degrade after use and disposal, and no obvious direct degradation of aromatic polyesters such as PET and PBT by microorganisms has been observed so far.

[0003] As an environmentally friendly plastic, aliphatic polyesters have attracted attention. Aliphatic polyesters can be obtained by esterification reaction and melt polycondensation reaction of aliphatic dicarboxylic acids and aliphatic diols. The raw aliphatic dicarboxylic acids (such as succinic acid and adipic acid) can be produced by fermentation from glucose derived from plants, and aliphatic diols (such as ethylene glycol, propylene glycol, and butanediol) can also be produced from raw materials derived from plants, so it is possible to seek to save fossil fuel resources. At the same time, since the growth of plants can absorb carbon dioxide in the atmosphere, it can make a greater contribution to reducing carbon dioxide emissions. Furthermore, it is also known that aliphatic polyesters show excellent biodegradability, and it can be said that they are triple environmentally friendly plastics.

[0004] However, products made of aliphatic polyesters often have problems such as precipitation of small molecules on the surface and loss of gloss. To solve this problem, JP2004107457A uses acetone to clean polyester particles, and JP3396537B2 uses methanol or isopropanol to clean polyester particles. Although these methods can improve the gloss of polyester to a certain extent, they add multiple steps and increase costs. In addition, these organic solvents may remain in the polyester particles and cause new small molecule problems. On the other hand, the use of alcohols may cause polyester degradation, molecular weight reduction and other problems. CN101910245B improves the gloss of polyester products by controlling the wall temperature of the distillation tube of the polycondensation reactor and the internal temperature of the polycondensation reactor, but the degree of improvement is still limited.

[0005] On the other hand, the melt viscosity of aliphatic polyester is relatively high, and the injection molding of fine parts is prone to problems such as melt glue shortage, making improving the fluidity of aliphatic polyester an important issue for technicians in this field. Summary of the invention

[0006] In order to overcome the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a polyester having a specific content of low molecular weight substances, which not only solves the problem of easy precipitation on the surface of polyester products, but also improves the fluidity of the polyester resin, so that the gloss and fluidity of the product are maintained in a balanced state.

[0007] Another object of the present invention is to provide a method for preparing the above polyester.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A polyester comprising repeating units derived from:

[0010] The first component A, based on the total molar amount of the first component A, comprises:

[0011] a1) 81 to 100 mol %, preferably 90-100 mol % of succinic acid or its ester derivatives or its anhydride derivatives;

[0012] a2) 0 to 19 mol %, preferably 0-10 mol % of other dicarboxylic acids other than succinic acid or their ester derivatives or their anhydride derivatives;

[0013] The second component B, 1,4-butanediol;

[0014] Among them, based on the total weight of the polyester, the total content of low molecular weight substances in the polyester is 0.1-0.6wt%, preferably 0.2-0.5wt%, and the GPC curve of the low molecular weight substances has the following characteristics: the integral area of ​​the peak with a number average molecular weight Mn greater than 400 is less than 60% of the total integral area.

[0015] The total content of the low molecular weight substances is tested according to the following method:

[0016] 10 g of polyester particles (the mass of the polyester particles is recorded as wg) are placed in 100 ml of ethanol and heated to reflux for 4 h. The filtrate is filtered while hot and poured into a pre-weighed evaporating dish. The weight of the evaporating dish is recorded as a0. The filtrate is evaporated to near dryness on a water bath. The evaporating dish is moved into a 105°C oven and dried for 2 h. The evaporating dish is then taken out and weighed after cooling for 0.5 h, which is recorded as a1. The content of low molecular weight substances = (a1-a0) / w×100%.

[0017] Low molecular weight substances in polyester are cyclic esters produced during the synthesis of polyester, mainly including cyclic dimers and cyclic polymers with more than 2 repeating units. The present invention controls the total content of low molecular weight substances in polyester to 0.1-0.6wt%, and at the same time, the integral area of ​​the peak (cyclic polymer) with a number average molecular weight Mn greater than 400 of the GPC curve of the low molecular weight substances is less than 60% of the total integral area, thereby improving the precipitation problem of polyester and improving its fluidity, and the prepared polyester product has high gloss and good fluidity. If the total content of low molecular weight substances in polyester is too high, it will cause serious precipitation problems and poor gloss during subsequent processing and use; if the total content of low molecular weight substances is too low, it cannot play the role of a flow modifier, affecting the improvement of polyester fluidity.

[0018] As a further technical solution of the present invention, the total content of low molecular weight substances in the polyester is 0.2-0.35wt%, and the GPC curve of the low molecular weight substances has the following characteristics: the integral area of ​​the peak with a number average molecular weight Mn greater than 400 is less than 50% of the total integral area.

[0019] Preferably, the first component A is succinic acid or its ester derivative or its anhydride derivative.

[0020] As a specific example, the component a2) is selected from oxalic acid, dimethyl oxalate, malonic acid, dimethyl malonate, methylsuccinic acid, glutaric acid, dimethyl glutarate, bis(2-hydroxyethyl) glutarate, bis(3-hydroxypropyl) glutarate, bis(4-hydroxybutyl) glutarate, 2-methylglutaric acid, 3-methylglutaric acid, adipic acid, dimethyl adipate, bis(2-hydroxyethyl) adipate, bis(3-hydroxypropyl) adipate, bis(4-hydroxybutyl) adipate, 3-methyladipic acid, 2,2,5,5-tetramethyladipic acid, pimelic acid, suberic acid, azelaic acid, dimethyl azelate, sebacic acid, 1,11-undecanedicarboxylic acid, 1,10-decanedicarboxylic acid, undecanedicarboxylic acid, 1,12-Dodecanedicarboxylic acid, hexadecanedioic acid, eicosanedioic acid, tetracosanoic acid, dimer acid, terephthalic acid, dimethyl terephthalate, bis(2-hydroxyethyl) terephthalate, bis(3-hydroxypropyl) terephthalate, bis(4-hydroxybutyl) terephthalate Esters, isophthalic acid, dimethyl isophthalate, bis(2-hydroxyethyl) isophthalate, bis(3-hydroxypropyl) isophthalate, bis(4-hydroxybutyl) isophthalate, 2,6-naphthalenedicarboxylic acid, dimethyl 2,6-phthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, dimethyl 2,7-phthalenedicarboxylic acid, 3,4′-diphenyl ether dicarboxylic acid, dimethyl 3,4′-diphenyl ether dicarboxylic acid, 4,4′-diphenyl ether dicarboxylic acid, dimethyl 4,4′-diphenyl ether dicarboxylic acid, 3,4′-phenylene sulfide dicarboxylic acid, dimethyl 3,4′-phenylene sulfide dicarboxylic acid, 4,4′-diphenyl sulfide dicarboxylic acid, dimethyl 4,4′-phenylene sulfide dicarboxylic acid, 3,4′-diphenyl sulfone dicarboxylic acid, 3,4′- One or more of dimethyl diphenyl sulfone dicarboxylate, 4,4′-diphenyl sulfone dicarboxylic acid, 4,4′-diphenyl sulfone dicarboxylic acid dimethyl ester, 3,4′-benzophenone dicarboxylic acid, 3,4′-benzophenone dicarboxylic acid dimethyl ester, 4,4′-benzophenone dicarboxylic acid, 4,4′-benzophenone dicarboxylic acid dimethyl ester, 1,4-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid dimethyl ester, 4,4′-methylene bis(benzoic acid), 4,4′-methylene bis(benzoic acid dimethyl ester) or their ester derivatives or their anhydride derivatives, preferably one or more of adipic acid, sebacic acid, 1,12-dodecane dicarboxylic acid, terephthalic acid or their ester derivatives or their anhydride derivatives, more preferably one or more of adipic acid, sebacic acid, terephthalic acid or their ester derivatives or their anhydride derivatives, most preferably adipic acid, terephthalic acid or their ester derivatives or their anhydride derivatives.

[0021] In the present invention, if necessary, the polyester further comprises a third component C, which is a compound containing at least three functional groups, preferably selected from one or more of tartaric acid, citric acid, malic acid, fumaric acid, maleic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyether triol, glycerol, 1,3,5-trimethylol acid, 1,2,4-trimethylol acid, 1,2,4-trimethylol anhydride, 1,2,4,5-pyromellitic acid or pyromellitic dianhydride, more preferably one or more of malic acid, citric acid, fumaric acid, maleic acid or glycerol;

[0022] Preferably, based on the total molar amount of the first component A, the content of the third component C is 0.01-1.0 mol%, preferably 0.02-0.2 mol%.

[0023] In the present invention, if necessary, the polyester further comprises a fourth component D, and the fourth component D is a chain extender.

[0024] The chain extender is selected from one or more of isocyanates, isocyanurates, peroxides, epoxides, oxazolines, oxazines, lactams, carbodiimides and polycarbodiimides containing two or more functional groups, preferably isocyanates containing two or more functional groups, more preferably hexamethylene diisocyanate.

[0025] The isocyanate containing two or more functional groups may be an aromatic isocyanate or an aliphatic isocyanate, preferably an aromatic diisocyanate or an aliphatic diisocyanate. Preferably, the aromatic diisocyanate is preferably toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate, diphenylmethane 4,4'-diisocyanate, naphthalene 1,5-diisocyanate or xylene diisocyanate. More preferably, the aromatic diisocyanate is diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate or diphenylmethane 4,4'-diisocyanate.

[0026] Preferably, the aliphatic diisocyanate is preferably any linear or branched alkylene diisocyanate or cycloalkylene diisocyanate containing 2 to 20 carbon atoms. More preferably, it is any linear or branched alkylene diisocyanate or cycloalkylene diisocyanate containing 3 to 12 carbon atoms. The aliphatic diisocyanate may be hexamethylene 1,6-diisocyanate, isophorone diisocyanate or methylene di(4-isocyanatocyclohexane). Most preferably, it is hexamethylene 1,6-diisocyanate or isophorone diisocyanate.

[0027] The isocyanate containing two or more functional groups may also be tris(4-isocyanato-phenyl)methane having three rings.

[0028] Preferably, the isocyanurate containing 2 or more functional groups is an aliphatic isocyanurate selected from alkylene diisocyanates or cycloalkylene diisocyanates having 2 to 20 carbon atoms, preferably 3 to 12 carbon atoms, such as isophorone diisocyanate or methylene di(4-isocyanatocyclohexane). The alkylene diisocyanate may be a linear or branched compound. Particularly preferred are isocyanurates based on cyclic trimers, pentamers or higher oligomers of n-hexamethylene diisocyanate such as hexamethylene 1,6-diisocyanate.

[0029] Preferably, the peroxide containing two or more functional groups is preferably benzoyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)methylcyclododecane, 4,4-di(butylperoxy)butyl valerate, dicumyl peroxide, tert-butyl peroxybenzoate, dibutyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne or tert-butyl peroxide cumene.

[0030] Preferably, the epoxide containing two or more functional groups is preferably hydroquinone, diglycidyl ether, resorcinol diglycidyl ether, 1,6-hexanediol diglycidyl ether and hydrogenated bisphenol A diglycidyl ether, terephthalic acid diglycidyl ester, tetrahydrophthalic acid diglycidyl ester, hexahydrophthalic acid diglycidyl ester, phthalic acid dimethyl diglycidyl ester, phenylene diglycidyl ether, ethylene diglycidyl ether, trimethylene diglycidyl ether, tetramethylene diglycidyl ether, hexahydrophthalic acid diglycidyl ether, Methyl diglycidyl ether, sorbitol diglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether or polybutylene glycol diglycidyl ether.

[0031] The epoxide containing 2 or more functional groups is also preferably a copolymer based on styrene, acrylate and / or methacrylate and containing epoxy groups, and the epoxy groups are preferably glycidyl methacrylate. Advantageous compounds have been shown to be copolymers in which the proportion of glycidyl methacrylate in the copolymer is higher than 20% by weight, more preferably higher than 30% by weight, more preferably higher than 50% by weight. The epoxy equivalent weight in these copolymers is preferably 150 to 3000 g / equivalent, more preferably 200 to 500 g / equivalent. The weight average molecular weight Mw of the copolymer is preferably 2000 to 25000, more preferably 3000 to 8000. The number average molecular weight Mn of the copolymer is preferably 400 to 6000, more preferably 1000 to 4000. The polydispersity index (Q=Mw / Mn) is preferably 1.5 to 5.

[0032] The oxazoline or oxazine having two or more functional groups is preferably dioxazoline or dioxazine, and the bridging part thereof is a single bond, (CH2)z-alkylene, wherein z=2, 3 or 4, such as methylene, 1,2-diyl, 1,3-diyl or 1,2-diyl, or phenylene. Specifically, the dioxazoline is 2,2'-bis(2-oxazoline), bis(2-oxazoline)methane, 1,2-bis(2-oxazoline)ethane, 1,3-bis(2-oxazoline)propane, 1,4-bis(2-oxazoline)butane, 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(4,4'-dimethyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline), 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis(4-butyl-2-oxazoline), 2,2'-bis(4-hexyl-2-oxazoline), 2,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexyl-2-oxazoline), 2,2' -bis(4-benzyl-2-oxazoline), 2,2'-p-phenylenebis(4-methyl-2-oxazoline), 2,2'-p-phenylenebis(4,4'-dimethyl-2-oxazoline), 2,2'-m-phenylenebis(4-methyl-2-oxazoline), 2,2'-m-phenylenebis(4,4'-dimethyl-2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2 '-octamethylenebis(2-oxazoline), 2,2'-decamethylenebis(2-oxazoline), 2,2'-ethylenebis(4-methyl-2-oxazoline), 2,2'-tetramethylenebis(4,4'-dimethyl-2-oxazoline), 2,2'-9,9'-diphenoxyethanebis(2-oxazoline), 2,2'-cyclohexylenebis(2-oxazoline) or 2,2'-diphenylene(2-oxazoline).

[0033] Specifically, the dioxazine is 2,2′-di(2-dioxazine), di(2-dioxazinyl)methane, 1,2-di(2-dioxazinyl)ethane, 1,3-di(2-dioxazinyl)propane, 1,4-di(2-dioxazinyl)butane, 1,4-di(2-dioxazinyl)benzene, 1,2-di(2-dioxazinyl)benzene or 1,3-di(2-dioxazinyl)benzene.

[0034] The carbodiimide or polycarbodiimide having two or more functional groups is preferably N,N′-di-2,6-diisopropylphenylcarbodiimide, N,N′-di-o-tolylcarbodiimide, N,N′-diphenylcarbodiimide, N,N′-dioctyldecylcarbodiimide, N,N′-di-2,6-dimethylphenylcarbodiimide, N-tolyl-N′-cyclohexylcarbodiimide, N,N′-di-2,6-di-tert-butylphenylcarbodiimide, N-tolyl-N′-phenylcarbodiimide, N,N′-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-dicyclohexylcarbodiimide, N,N'-di-p-tolylcarbodiimide, p-phenylenebis-o-tolylcarbodiimide, p-phenylenebis-dicyclohexylcarbodiimide, hexamethylenebis-dicyclohexylcarbodiimide, 4,4'-dicyclohexylmethanecarbodiimide, ethylenebis-diphenylcarbodiimide, N,N'-benzyl-carbodiimide, N-octadecyl-N'-phenylcarbodiimide, N-benzyl-N'-phenylcarbodiimide, N-octadecyl N-phenyl-N'-tolylcarbodiimide, N-cyclohexyl-N'-tolylcarbodiimide, N-phenyl-N'-tolylcarbodiimide, N-benzyl-N'-tolylcarbodiimide, N,N'-di-o-ethylphenylcarbodiimide, N,N'-di-p-ethylphenylcarbodiimide, N,N'-di-o-isopropylphenylcarbodiimide, N,N'-di-p-isopropylphenylcarbodiimide, N,N'-di-o-isobutylphenylcarbodiimide, N,N'-di-p-isobutylphenylcarbodiimide, N,N'-di-2,6-diethylphenylcarbodiimide , N,N′-di-2-ethyl-6-isopropylphenylcarbodiimide, N,N′-di-2-isobutyl-6-isopropylphenylcarbodiimide, N,N′-di-2,4,6-trimethylphenylcarbodiimide, N,N′-di-2,4,6-triisopropylphenylcarbodiimide, N,N′-di-2,4,6-triisopropylphenylcarbodiimide, N,N′-di-2,4,6-triisobutylphenylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, di-β-naphthylcarbodiimide or di-tert-butylcarbodiimide.

[0035] Preferably, based on the total molar amount of the first component A, the content of the fourth component D is 0.01-5.0 mol %.

[0036] Preferably, the viscosity of the polyester measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05° C. according to GB / T 17931-1999 is 100-350 ml / g.

[0037] The present invention also provides a method for preparing the above polyester, comprising the following steps:

[0038] S1: After mixing the first component A, the second component B and part of the catalyst, heat to 180-260° C. in an esterification reactor for esterification reaction for 1-4 hours to obtain an esterification product AB;

[0039] S2: subjecting the esterification product AB in step S1 to a primary polycondensation reaction at a reaction temperature of 200-240° C. for a reaction time of 2-6 h to obtain a primary polycondensation product Pre-AB;

[0040] S3: The primary polycondensation product Pre-AB obtained in step S2 and the remaining catalyst are transferred to a final polymerization kettle, and the polycondensation reaction is continuously carried out at a temperature of 210°C-270°C until the reaction product reaches a viscosity of 100-350 ml / g as specified in GB / T 17931-1999 measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C.

[0041] Preferably, in step S1, the amount of the second component 1,4-butanediol added is generally 1.3-3.0 times (molar amount) of the first component A diacid, preferably 1.5-2.5 times (molar amount).

[0042] Preferably, in step S1, when preparing the AB esterification product, 0.001-1% of the catalyst based on the weight of the final polyester is added. Preferably, the amount of the catalyst added is 0.02-0.2% of the weight of the final polyester. The amount of catalyst added in step S1 is generally 10-40wt% of the total amount of catalyst used. Controlling the amount of catalyst added can make the subsequent processing process more stable. Further, the catalyst can be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound or a titanium compound, more preferably a zinc compound, an aluminum compound or a titanium compound, and most preferably a titanium compound. Titanium compounds such as tetrabutyl orthotitanate or tetraisopropyl orthotitanate have the advantage of being less toxic in the residual amount remaining in the product or downstream product relative to other compounds. This property is particularly important in biodegradable polyesters because they can enter the environment directly in the form of compost bags or mulch films.

[0043] In step S2, the reaction temperature is more preferably 210-230° C. In step S2, the pressure at the start is usually set to 0.1 to 0.5 bar, preferably 0.2 to 0.4 bar, and the pressure at the end of S2 is usually set to 5 to 200 mbar, more preferably 10 to 100 mbar.

[0044] The process of the present invention can catalyze the polymerization of cyclic esters in this stage into linear high molecular weight polyesters by adding a specific amount of catalyst in the polycondensation stage of step S3, thereby effectively reducing the content of cyclic esters, especially reducing the content of cyclic polymers with a repeating unit number exceeding 2, so that the total content of low molecular weight substances in the polyester does not exceed 0.6 wt%, and at the same time, the integral area of ​​the peak (cyclic dimer) with a number average molecular weight Mn greater than 400 in the GPC curve of the low molecular weight substances can be controlled to be less than 60% of the total integral area.

[0045] The present invention shows that the amount of catalyst added in step S3 directly affects the total content of low molecular weight substances in polyester. If the amount of catalyst added in step S3 is too small, it will not effectively reduce the total content of low molecular weight substances. Preferably, in step S3, the amount of catalyst added is 60-90wt% of the total amount of catalyst.

[0046] In step S3, the reaction temperature of the continuous polycondensation is preferably 230 to 260° C. In step S3, the pressure at the beginning is usually controlled to be 0.2 to 5 mbar, more preferably 0.5 to 3 mbar. The reaction time of the continuous polycondensation is preferably 2-7 hours, more preferably 3-6 hours. The carboxyl content in the polyester after the S3 reaction is preferably 20-60 mmol / kg.

[0047] If necessary, after step S3, step S4 is performed, wherein the polyester obtained in step S3 is added into a twin-screw extruder, together with 0.01-5.0 mol % of the chain extender fourth component D (based on the total molar amount of the first component A), at a reaction temperature of 200 to 270° C. and a residence time of 0.5 to 15 minutes to obtain a polyester having a viscosity of 150-350 ml / g as measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05° C. as specified in GB / T 17931-1999.

[0048] In another aspect, the present invention further provides a polyester molding composition, comprising the following components by weight:

[0049] 5-95wt% of the above polyester;

[0050] 5-95wt% additives and / or other polymers;

[0051] 0-70wt% reinforcement and / or filler.

[0052] As a specific option, the additive and / or other polymer may be at least one or more components selected from aliphatic polyester, polycaprolactone, starch, cellulose, polyhydroxyalkanoate and polylactic acid.

[0053] In another aspect, the present invention further provides the use of the polyester in preparing a compostable product, wherein the compostable product may be a fiber, a film or a container.

[0054] The invention also provides application of the polyester in preparing straws.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The present invention provides a polyester, in which the total content of low molecular weight substances is controlled within the range of 0.1-0.6wt%, and the integral area of ​​the peak of the GPC curve of the low molecular weight substances with a number average molecular weight Mn greater than 400 is less than 60% of the total integral area. The polyester can effectively solve the problem of easy precipitation on the surface of polyester products, and the prepared polyester product has high gloss. At the same time, the fluidity of the polyester resin can be improved, so that the gloss and fluidity of the product are maintained in a balanced state. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is the GPC curve of the low molecular weight substance in Example 1 of the present invention.

[0058] Figure 2 This is the GPC curve of the low molecular weight substance in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0059] Unless otherwise specified, raw materials, reagents and solvents used in the present invention are all purchased commercially without any treatment. Below in conjunction with embodiment, the present invention is described in further detail, but embodiments of the present invention are not limited by following examples, and any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should all be equivalent replacement modes, and are all included in protection scope of the present invention. In addition, about "part", "%" in this specification, unless otherwise specified, represent "mass parts", "mass %" respectively.

[0060] The raw materials used in the examples and comparative examples of the present invention are all commercially available.

[0061] Test method:

[0062] Viscosity of polyester:

[0063] According to GB / T 17931-1999, the sample concentration is 5 mg / ml in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05℃.

[0064] Content of low molecular weight substances:

[0065] About 10 g of polyester particles, the mass of which is recorded as wg, are placed in 100 ml of ethanol and heated to reflux for 4 h. The filtrate is filtered while hot and poured into a pre-weighed evaporating dish (recorded as a0). The filtrate is evaporated to near dryness on a water bath. The evaporating dish is moved into an oven at 105°C and dried for 2 h. The evaporating dish is then taken out and weighed after cooling for 0.5 h (recorded as a1). The content of low molecular weight substances = (a1-a0) / w×100%.

[0066] GPC test of low molecular weight substances:

[0067] GPC was tested using Waters' ACQUITY APC™ equipment at 40°C, using XT45, XT200 and XT459 columns, solvent: tetrahydrofuran, mobile phase flow rate: 0.5 mL / min. Polystyrene standards were used as standard samples. About 10 g of polyester particles were placed in 100 ml of ethanol and heated to reflux for 4 h. The filtrate was filtered while hot and poured into an evaporating dish and placed on a water bath to evaporate to near dryness. The evaporating dish was moved into a 105°C oven and dried for 2 h, then the evaporating dish was removed and cooled for 0.5 h. The substance in the evaporating dish was a low molecular weight substance. The low molecular weight substance was prepared into a solution of about 0.5 mg / mL and then injected for testing.

[0068] Gloss test:

[0069] After the polyester particles were dried at 80°C for 5 hours, they were injection molded into 100*100*2mm square plates at 160°C, and then the L value of the square plates was tested using an X-Rite Color Eye 7000A desktop spectrophotometer. The larger the L value, the higher the glossiness.

[0070] Refer to GB / T 3682.1-2018 Plastics Thermoplastics Melt Mass Flow Rate (MFR) and Melt Volume Flow Rate (MVR) Determination Part 1: Standard Method, test the melt index MFR of polyester. Test temperature 190 o C, load 2.16 kg, melting time 5 min.

[0071] Example 1

[0072] S1: 800 kg / h of succinic acid, 1038 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.104 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200°C for 60-120 minutes to obtain an esterification product AB.

[0073] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar, heated to 220°C, the reaction time is 3-5 hours, the pressure drops to 100 mbar, and most of the excess 1,4-butanediol is distilled off to obtain the prepolymer product Pre-AB.

[0074] S3: The prepolymer product Pre-AB and 0.587 kg / h of tetrabutyl orthotitanate were transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products were distilled off. Then, the polyester was granulated with an underwater granulator and then dried to obtain the final polyester product. The integral ratio of each peak in the GPC curve of the low molecular weight substance is shown in Table 1, and the performance results are shown in Table 3.

[0075] Table 1 Integration ratio of each peak in the GPC curve

[0076]

[0077] Example 2

[0078] S1: 800 kg / h of succinic acid, 1038 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.207 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0079] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar, heated to 220°C, the reaction time is 3-5 hours, the pressure drops to 100 mbar, and most of the excess 1,4-butanediol is distilled off to obtain the prepolymer product Pre-AB.

[0080] S3: The prepolymer product Pre-AB and 0.483 kg / h of tetrabutyl orthotitanate were transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products were distilled off. Then, the polyester was granulated with an underwater granulator and then dried to obtain the final polyester product. The performance results are shown in Table 3.

[0081] Example 3

[0082] S1: 800 kg / h of succinic acid, 1038 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.207 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0083] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar, heated to 220°C, the reaction time is 3-5 hours, the pressure drops to 100 mbar, and most of the excess 1,4-butanediol is distilled off to obtain the prepolymer product Pre-AB.

[0084] S3: The prepolymer product Pre-AB and 0.483 kg / h of tetrabutyl orthotitanate are transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products are distilled off to obtain the final polymer Poly-AB.

[0085] S4: Poly-AB final polymer was continuously fed into a twin-screw extruder, and 6.3 kg / h of hexamethylene diisocyanate (HDI) was metered in at the same time, and the temperature was set to 240° C. After a residence time of 3 minutes, the polyester was pelletized with an underwater pelletizer and then dried to obtain the final polyester product. The performance results are shown in Table 3.

[0086] Example 4

[0087] The catalyst is tetraisopropyl orthotitanate. The amount of catalyst added in step S1 is 0.087 kg / h, and the amount of catalyst added in step S3 is 0.490 kg / h.

[0088] The rest is the same as in Example 1. The performance results are shown in Table 3.

[0089] Example 5

[0090] S1: 800 kg / h of succinic acid, 855 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.207 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0091] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar, heated to 220°C, the reaction time is 3-5 hours, the pressure drops to 100 mbar, and most of the excess 1,4-butanediol is distilled off to obtain the prepolymer product Pre-AB.

[0092] S3: The prepolymer product Pre-AB and 0.483 kg / h of tetrabutyl orthotitanate were transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products were distilled off. Then, the polyester was granulated with an underwater granulator and then dried to obtain the final polyester product. The performance results are shown in Table 3.

[0093] Example 6

[0094] S1: 800 kg / h of succinic acid, 1526 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.207 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0095] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar, heated to 220°C, the reaction time is 3-5 hours, the pressure drops to 100 mbar, and most of the excess 1,4-butanediol is distilled off to obtain the prepolymer product Pre-AB.

[0096] S3: The prepolymer product Pre-AB and 0.483 kg / h of tetrabutyl orthotitanate were transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products were distilled off. Then, the polyester was granulated with an underwater granulator and then dried to obtain the final polyester product. The performance results are shown in Table 3.

[0097] Example 7

[0098] The amount of catalyst added in step S1 is 0.242 kg / h, and the amount of catalyst added in step S3 is 0.449 kg / h.

[0099] The rest is the same as in Example 5. The performance results are shown in Table 3.

[0100] Comparative Example 1

[0101] S1: 800 kg / h of succinic acid, 1038 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.449 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0102] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar and heated to 220°C. 0.242 kg / h of tetrabutyl orthotitanate is added to the reactor. The reaction time is 3-5 hours. The pressure drops to 100 mbar. Most of the excess 1,4-butanediol is distilled off to obtain a prepolymer product Pre-AB.

[0103] S3: The prepolymer product Pre-AB is transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products are distilled off. Then, the polyester is granulated with an underwater granulator and then dried to obtain the final polyester product. The integral ratio of each peak in the GPC curve of the low molecular weight substance is shown in Table 2, and the performance results are shown in Table 3.

[0104] Table 2 Integral ratio of each peak in GPC curve

[0105]

[0106] Comparative Example 2

[0107] The PBS resin obtained in Comparative Example 1 was subjected to solvent extraction using an ultrasonic countercurrent extractor (ND-400, produced by Jiangsu Huatai Heavy Industry Equipment Co., Ltd.). The key process parameters are as follows:

[0108] Feed rate: 500 kg / h;

[0109] Solvent (volume ratio: ethanol / water = 80 / 20);

[0110] Extraction temperature: 70℃;

[0111] Residence time: 2.5h;

[0112] After the material is discharged, it is dried and cooled to obtain a PBS resin with a low content of low-molecular substances. The ethanol content thereof is detected to be 70 ppm.

[0113] Test method: Weigh 1.2000±0.0200g sample, add it to the sample bottle, and use Agilent 7697A-7890A static headspace gas chromatograph as the test equipment for quantification, expressed as mass ppm relative to the sample. Static headspace conditions: 105℃, 2h. Chromatographic column: J&W 122-7032: 250℃: 30m*250μm*0.25μm. GC heating program: initial value 50℃, holding time: 3 minutes; heating to 200℃, heating rate 12℃ / min, holding time: 4 minutes.

[0114] Comparative Example 3

[0115] S1: 800 kg / h of succinic acid, 1038 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.207 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0116] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar and heated to 220°C. 0.483 kg / h of tetrabutyl orthotitanate is added to the reactor. The reaction time is 3-5 hours. The pressure drops to 100 mbar and most of the excess 1,4-butanediol is distilled off to obtain a prepolymer product Pre-AB.

[0117] S3: The prepolymer product Pre-AB is transferred to a final polymerization reactor and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products are distilled off. Then, the polyester is granulated with an underwater granulator and then dried to obtain the final polyester product. The performance results are shown in Table 3.

[0118] Comparative Example 4

[0119] Referring to the polymerization process of Example 1 of CN101910245B, the following experiment was carried out:

[0120] S1: 800 kg / h of succinic acid, 916 kg / h of 1,4-butanediol and 3.0 kg / h of malic acid are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0121] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar and heated to 220°C. 0.46 kg / h of tetrabutyl orthotitanate is added to the reactor. The reaction time is 3-5 hours. The pressure drops to 100 mbar and most of the excess 1,4-butanediol is distilled off to obtain a prepolymer product Pre-AB.

[0122] S3: The prepolymer product Pre-AB is transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C (temperature t2 in the reactor) and a pressure of 1mbar. The remaining excess 1,4-butanediol and other by-products are distilled out, and the wall temperature T of the distillation tube is 200°C. After the distillate is condensed, it is supplied to the esterification reactor at a rate of 4.2 kg / h through a pipeline insulated with a heat medium jacket (130°C). Then, the polyester is granulated with an underwater granulator and then dried to obtain the final polyester product. The performance results are shown in Table 3.

[0123] Comparative Example 5

[0124] S1: 800 kg / h of succinic acid, 1038 kg / h of 1,4-butanediol, 0.93 kg / h of glycerol and 0.449 kg / h of tetrabutyl orthotitanate are physically mixed in an esterification reactor at room temperature, and then the mixture is subjected to an esterification reaction at 200° C. for 60-120 minutes to obtain an esterification product AB.

[0125] S2: The esterification product AB passes through a static mixer and then enters a vertical stirring fully mixed reactor. The initial pressure is 0.3 bar, heated to 220°C, the reaction time is 3-5 hours, the pressure drops to 100 mbar, and most of the excess 1,4-butanediol is distilled off to obtain the prepolymer product Pre-AB.

[0126] S3: The prepolymer product Pre-AB and 0.242 kg / h of tetrabutyl orthotitanate were transferred to a final polymerization reactor, and polycondensed for 3-5 hours at a temperature of 240°C and a pressure of 1 mbar. The remaining excess 1,4-butanediol and other by-products were distilled off. Then, the polyester was granulated with an underwater granulator and then dried to obtain the final polyester product. The performance results are shown in Table 3.

[0127] Table 3 Performance results

[0128]

[0129] Table 3

[0130]

[0131] It can be seen from the results in Table 3 that the total content of low molecular weight substances in Examples 1-7 of the present invention is controlled at 0.1-0.6wt%, and the integral area of ​​the part (cyclic polymer) with a number average molecular weight greater than 400 of the GPC curve of the low molecular weight substances is controlled to be less than 60% of the total integral area. The gloss L of the prepared polyester product can reach above 79, with high gloss and good fluidity, and the gloss and fluidity are maintained in a balanced state.

[0132] Comparative Example 1 or 3 uses the traditional catalyst addition process, and all the catalysts are added in steps S1 and S2, which cannot effectively reduce the content of low molecular weight substances. The total content of low molecular weight substances in the prepared polyester and the integral area of ​​the part of the GPC curve of the low molecular weight substances with a number average molecular weight greater than 400 (cyclic polymers) are not within the scope of the present invention. Although the fluidity is good, the gloss of the obtained polyester product is poor, and the balance between fluidity and gloss cannot be achieved.

[0133] Comparative Example 2: Using a mixed solvent of ethanol / water to clean the PBS resin obtained in Comparative Example 1 can effectively reduce the total content of low molecular weight substances, but the content of low molecular weight substances is too low, the fluidity of the product is very poor, and the balance between fluidity and gloss cannot be achieved. In addition, the resin contains more ethanol, causing secondary pollution.

[0134] Comparative Example 4 refers to the polymerization process of Example 1 of CN101910245B, controls the temperature of the equipment process related to the final polymerization reactor, and controls the total content of low molecular weight substances in the prepared polyester at 0.51%. However, since this process control mainly solves the cyclic dimer, the reduction of cyclic polymers is relatively limited, and the integral area of ​​the part of the GPC curve of the low molecular weight substance with a number average molecular weight greater than 400 (cyclic polymers) is also not within the scope of the present invention, and the gloss of the obtained polyester product is also poor.

[0135] In Comparative Example 5, the total content of low molecular weight substances and the integrated area of ​​the portion with a number average molecular weight greater than 400 (cyclic polymer) in the GPC curve are both high, and the glossiness of the obtained polyester product is also poor, and a balance between fluidity and glossiness cannot be achieved;

[0136] It can be seen from the results of Examples 1-7 and Comparative Examples 1-5 that the prepared polyester product cannot simultaneously meet the conditions that the total content of low molecular weight substances is in the range of 0.1-0.6wt% and the integral area of ​​the peak with a number average molecular weight Mn greater than 400 on the GPC curve accounts for less than 60% of the total integral area, and the gloss and fluidity of the obtained polyester product cannot be taken into account at the same time.

Claims

1. A polyester comprising repeating units derived from: The first component A, based on the total molar amount of the first component A, comprises: a1) 81 to 100 mol % of succinic acid or its ester derivative or its anhydride derivative; a2) 0 to 19 mol % of other dicarboxylic acids other than succinic acid or their ester derivatives or acids thereof Anhydride derivatives; The second component B, 1,4-butanediol; Characterized in that, based on the total weight of the polyester, the total content of low molecular weight substances in the polyester is 0.1-0.6wt%, and the GPC curve of the low molecular weight substances has the following characteristics: the integral area of ​​the peak with a number average molecular weight Mn greater than 400 is less than 52% of the total integral area, The total content of the low molecular weight substances is tested according to the following method: 10 g of polyester particles (the mass of polyester particles is recorded as wg) were placed in 100 ml of ethanol and heated under reflux for 4 h. Get the filtrate, pour the filtrate into a pre-weighed evaporating dish, the weight of the evaporating dish is recorded as a0, place the filtrate on a water bath and evaporate it to near dryness, move the evaporating dish into a 105℃ oven and dry it for 2h, then take out the evaporating dish, cool it for 0.5h and weigh it, recorded as a1, then the content of low molecular weight substance = (a1-a0) / w×100%.

2. The polyester according to claim 1, characterized in that The first component A, based on the total molar amount of the first component A, comprises: a1) 90-100 mol % of succinic acid or its ester derivative or its anhydride derivative; a2) 0-10 mol % of other dicarboxylic acids except succinic acid or their ester derivatives or their anhydride derivatives.

3. The polyester according to claim 1, characterized in that Based on the total weight of the polyester, the total content of low molecular weight substances in the polyester is 0.2-0.5wt%, and the GPC curve of the low molecular weight substances has the following characteristics: the integrated area of ​​the peak with a number average molecular weight Mn greater than 400 is less than 52% of the total integrated area.

4. The polyester according to claim 3, characterized in that The total content of low molecular weight substances in the polyester is 0.2-0.35 wt %, and the GPC curve of the low molecular weight substances has the following characteristics: the integrated area of ​​the peak with a number average molecular weight Mn greater than 400 is less than 50% of the total integrated area.

5. The polyester according to claim 1, characterized in that The first component A is succinic acid or its ester derivative or its anhydride derivative.

6. The polyester according to claim 1, characterized in that The polyester further comprises a third component C, which is a compound containing at least three functional groups; based on the total molar amount of the first component A, the content of the third component C is 0.01-1.0 mol%.

7. The polyester according to claim 6, characterized in that Based on the total molar amount of the first component A, the content of the third component C is 0.02-0.2 mol%.

8. The polyester according to claim 6, characterized in that The third component C is selected from one or more of tartaric acid, citric acid, malic acid, fumaric acid, maleic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyether triol, glycerol, 1,3,5-trimethylol acid, 1,2,4-trimethylol acid, 1,2,4-trimethylol anhydride, 1,2,4,5-pyromellitic acid or pyromellitic dianhydride.

9. The polyester according to claim 8, characterized in that The third component C is one or more of malic acid, citric acid, fumaric acid, maleic acid or glycerol.

10. The polyester according to claim 1, characterized in that The polyester further comprises a fourth component D, which is a chain extender; based on the total molar amount of the first component A, the content of the fourth component D is 0.01-5.0 mol%.

11. The polyester according to claim 10, characterized in that The fourth component D is selected from one or more of isocyanates, isocyanurates, peroxides, epoxides, oxazolines, oxazines, lactams, carbodiimides and polycarbodiimides containing two or more functional groups.

12. The polyester according to claim 11, characterized in that The fourth component D is an isocyanate containing 2 or more functional groups.

13. The polyester according to claim 12, characterized in that The fourth component D is hexamethylene diisocyanate.

14. The polyester according to claim 1, characterized in that The viscosity of the polyester measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05° C. according to GB / T 17931-1999 is 100-350 ml / g.

15. The method for preparing polyester according to any one of claims 1 to 14, characterized in that: The method comprises the following steps: S1: mixing the first component A, the second component B and part of the catalyst, heating the mixture to 180-260° C. in an esterification reactor for 1-4 hours to obtain an esterification product AB; S2: subjecting the esterification product AB in step S1 to a primary polycondensation reaction at a reaction temperature of 200-240° C. for a reaction time of 2-6 h to obtain a primary polycondensation product Pre-AB; S3: The primary polycondensation product Pre-AB obtained in step S2 and the remaining catalyst are transferred to the final polymerization reactor, and the polycondensation reaction is continued at a temperature of 210°C-270°C until the reaction product reaches the phenol / o-dichlorobenzene ratio of 1:1 as specified in GB / T 17931-1999. The viscosity number measured in a benzene solution in a constant temperature water bath at 25±0.05℃ is 100-350 ml / g; The amount of catalyst added in step S1 is 10-40wt% of the total amount of catalyst used, and the amount of catalyst added in step S3 is 60-90wt% of the total amount of catalyst used.

16. The method for preparing polyester according to claim 15, characterized in that: The catalyst is one or more of tin compounds, antimony compounds, cobalt compounds, lead compounds, zinc compounds, aluminum compounds or titanium compounds.

17. The method for preparing polyester according to claim 16, characterized in that: The catalyst is one or more of a zinc compound, an aluminum compound or a titanium compound.

18. The method for preparing polyester according to claim 17, characterized in that: The catalyst is tetrabutyl orthotitanate and / or tetraisopropyl orthotitanate.

19. A polyester molding composition, characterized in that In terms of weight percentage, the components include: 5-95wt% of the polyester according to any one of claims 1-14; 5-95wt% additives and / or other polymers; 0-70wt% reinforcement materials and / or fillers.

20. Use of the polyester according to any one of claims 1 to 14 in the preparation of compostable products, characterized in that: The compostable and degradable product is fiber, film or container.

21. Use of the polyester according to any one of claims 1 to 14 in the preparation of drinking straws.

Citation Information

Patent Citations

  • Method for producing aliphatic polyester

    CN101910245B

  • Aliphatic or alicyclic polyester and method for producing the same

    JP2004107457A

  • Method for cleaning aliphatic polyesters or compositions

    JP3396537B2

  • Polyester with low oligomer content and preparation method of polyester

    CN109369893A

  • Preparation method of poly (butylene succinate) with low cyclic byproduct

    CN114507338A